2017
DOI: 10.1590/abd1806-4841.20175318
|View full text |Cite
|
Sign up to set email alerts
|

Angiolymphoid hyperplasia with eosinophilia versus Kimura's disease: a case report and a clinical and histopathological comparison

Abstract: Angiolymphoid hyperplasia with eosinophilia is a rare and benign vascular tumor whose etiology remains uncertain. It clinically presents itself by angiomatous papules or nodules located on the head and neck. Many controversies in the literature are found in relation to angiolymphoid hyperplasia with eosinophilia and Kimura's disease - its main differential diagnosis - due to their clinical and histopathological similarities. However, currently, most studies agree that they are distinct diseases. The present ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 7 publications
1
25
0
1
Order By: Relevance
“…Adenolymphomas are often discovered during a superficial parotidectomy and exhibit marked enhancement in early stages. The density decreases rapidly in cases of delayed diagnosis and density may be heterogeneous in some cases (30). In the present study, low-density areas were observed in lesions.…”
Section: Eosinophil Granulocyte Count On Admissionsupporting
confidence: 48%
See 1 more Smart Citation
“…Adenolymphomas are often discovered during a superficial parotidectomy and exhibit marked enhancement in early stages. The density decreases rapidly in cases of delayed diagnosis and density may be heterogeneous in some cases (30). In the present study, low-density areas were observed in lesions.…”
Section: Eosinophil Granulocyte Count On Admissionsupporting
confidence: 48%
“…Pleomorphic adenomas and adenolymphomas are the most common benign tumors. Pleomorphic adenomas are often single, with delayed enhancement (30). Adenolymphomas are usually found in elderly males.…”
Section: Eosinophil Granulocyte Count On Admissionmentioning
confidence: 99%
“…It is a systemic immunological process characterized by lymphadenopathy, eosinophilia and increased serum levels of IgE. Renal disease and asthma are commonly present [7]. Histologically, florid lymphoid follicles and eosinophilic infiltrates are typical histological findings of Kimura disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis must be made between ALHE and Kimura disease which were thought to be the same pathology in the past [1, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Both share significant overlap in clinical symptoms (soft tissue masses in the head and neck region) but can be distinguished by both clinical and histologic features. Systemic manifestations are rarely found in ALHE and therefore kidney involvement is more suggestive for KD [128]. Coexisting renal disease is common in KD and described in about 12–18% of the patients with about two-thirds of them developing nephrotic syndrome [33].…”
Section: Eosinophilia In Kidney Diseasementioning
confidence: 99%